The Price Of Freedom: Iwadh Payments In Divorce Through Critical Legal Studies - Muhammad Aminuddin Shofi; Belgis Elisa Bela (UIN Sunan Kudus, 2026)
This article examines the governance of khuluk (wife-initiated divorce) in Indonesia’s legal system and its distinction from talak (husband-initiated divorce), or divorce initiated by the husband. Despite similar goal, khuluk requires the wife to pay iwadh (compensation) as economic exchange. Using a critical legal studies perspective, this research argues that khuluk and iwadh may reproduce gender inequality in contemporary Muslim society. The study employs normative legal research, drawing on conceptual and statute-based approaches, and uses documentation as the primary source of data. The data are analyzed through editing, classification, verification, interpretation, and conclusion drawing, with source triangulation used to ensure validity. The findings show that khuluk harms women because iwadh makes women seek khuluk under conditions of violence, pressure, or financial dependence, which weakens the idea of free consent. The article, therefore, calls for a progressive reinterpretation of khuluk to support gender justice and legal equity.